OC-061 Rates Of Post Colonoscopy Colorectal Cancer (pccrc) Are Significantly Affected By Methodology, But Are Nevertheless Declining In The Nhs. (9th June 2014) - Valori, R; Morris, E; Thomas, J; Rutter, M
Abstract : Introduction: It is recognised that post-colonoscopy colorectal cancer (PCCRC) can be due to missed cancer, or cancer arising from missed or incompletely removed polyps. Thus the rate of post-colonoscopy colorectal cancer (PCCRC) should become a key quality indicator of colonoscopy. A quality indicator should be relevant to patients, clearly defined, standardised, and measurable over time and have a target to aim for. This study compares methods for defining PCCRC rates, proposes a method that best meets these criteria and explores rates over time. Methods: Information on all individuals with a primary colorectal cancer and prior colonoscopic investigations in England between 2001 and 2010 was extracted from the National Cancer Data Repository. Previously published methods (Bressler, Cooper, Singh and leClerc) for deriving PCCRC rates were applied to these data to investigate the effect on the rate. A new method, based on the year of the colonoscopy, not CRC diagnosis, is proposed. Results: Of 297, 956 individuals diagnosed with colorectal cancer in the study period a total of 94, 648 underwent a colonoscopy in the 3 years prior to their diagnosis. The table illustrates how application of the published methods and exclusion criteria to the dataset produces significantly different PCCRC rates from 2.4 to 7.8%: The PCCRC rate of 6.8% produced by the Singh method best fulfils the proposed criteria for a quality indicator but it is not suitable for annual reporting: the rate reflects colonoscopy performance in the years preceding the year of reporting. Amending this method to look forward from the time of colonoscopy, rather than backward from the time of diagnosis of cancer, provides a rate relating to the year the procedure was actually performed. This new method demonstrates that PCCRC rates within 3 years of colonoscopy (without exclusions) decreased in the English NHS over 7 years by 29%: from 10.2 to 7.2% for colonoscopies performed in 2001 and 2007 respectively. 25% (37/148 hospitals) achieved a PCCRC for the period of 4.0% or less. Conclusion: PCCRC rates in England are improving over time and comparable to those in other countries. The method used to determine rates significantly affects findings, thus international benchmarking requires an agreed method for defining PCCRC. The Singh and suggested new method provide a PCCRC rate most relevant to patients. It is proposed that on the basis of current evidence, and improvements evident over time in this study, a reasonable target for a national rate of PCCRC up to 3 years following a colonoscopy should be less than 4%. Disclosure of Interest: None Declared.